Studied in Stability Constant of Lanthanum(III) and Samarium(III) Complexes with Valine in Non-Aqueous Medium - Suvarna, M.M.; Panse, V.S.; Fulwadva, U.P.; P.K. Jadhav, (Late) (Asian Journal of Chemistry, 2010)
Formation constants of lanthanum(III) and samarium(III) with L-valine have been determined pH-metrically using Irving-Rossotti titration technique adopted by Calvin and Bjerrum using various solvent systems at 28 ± 0.1ºC. The results are discussed in terms of effect of dielectric constant and mol fraction of solvent on proton-ligand stability constants and formation constants.